IMPLEMENTATION OF VALUE EDUCATION IN ISLAMIC RELIGIOUS EDUCATION - Amin Adi Prasetia (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This study aims to analyze the implementation of value education in Islamic Religious Education (PAI) in schools. This research focuses on understanding how Islamic values are taught, internalized, and applied in students' daily lives. Additionally, the study explores the factors that support and hinder the implementation of value education in the school environment. The research method used is a literature review. The findings show that value education in PAI has been implemented through various methods, such as role modeling, lectures, and group discussions. However, its implementation has not been optimal due to time constraints, materials that lack focus on value aspects, and insufficient support from students' social environment. These findings reveal that the integration of Islamic values with formal learning still requires improvement in terms of teaching approaches that are more practical and relevant to students' life contexts. The conclusion of this study indicates that value education in PAI has great potential in shaping students' character, but it requires more directed strategies and support from various parties, including families and communities. The study recommends a renewal of value-teaching methods in PAI to be more contextual and applicable to students.